2012
DOI: 10.1080/09243453.2011.652123
|View full text |Cite
|
Sign up to set email alerts
|

Student group differences in examination results and utilization for policy and school development

Abstract: At the end of secondary education in The Netherlands, students have to pass a final examination, consisting of an internal school-based assessment and an external national assessment. According to the Dutch inspectorate, to ensure the quality of final examinations, the discrepancy between both assessments must be less than 0.5 points (on a scale from 1 to 10). In the first part of this study, we demonstrate that these examination results are a rich source of data schools can use. We investigated the discrepanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 31 publications
2
18
0
2
Order By: Relevance
“…These better and positive changes all might imply that the project ALİS facilitated and increased the students' learning and personal development. These findings, therefore, might imply that the project ALİS contributed to the improvement process of the school and are congruent with the relevant literature, as Schildkamp et al (2012) claim that student success should enhanced real school development.…”
Section: Discussionsupporting
confidence: 85%
“…These better and positive changes all might imply that the project ALİS facilitated and increased the students' learning and personal development. These findings, therefore, might imply that the project ALİS contributed to the improvement process of the school and are congruent with the relevant literature, as Schildkamp et al (2012) claim that student success should enhanced real school development.…”
Section: Discussionsupporting
confidence: 85%
“…The literature shows that if teachers do not believe that data use can lead to improvement and instead rely on their experiences and intuition, and do not believe that data can actually reflect on their teaching, this can hinder the implementation of data use in schools (Datnow, Park, & Kennedy-Lewis, 2012;Hubbard, Datnow, & Pruyn, 2014;Schildkamp & Kuiper, 2010;Schildkamp, Rekers-Mombarg, & Harms, 2012;Schildkamp & Visscher, 2010;Wayman, Cho, Jimerson, & Spikes, 2012). However, if teachers believe in the utility of data use and the resulting improvement in the quality of their practice, this may enhance data use (Jimerson, 2014;Kerr, Marsh, Ikemoto, Darilek, & Barney, 2006;Schildkamp et al, 2012Schildkamp et al, , 2014Schildkamp & Visscher, 2009van der Kleij & Eggen, 2013;Vanhoof, Verhaeghe, Van Petegem, & Valcke, 2012;Yan & Cheng, 2015).…”
Section: Attitudementioning
confidence: 99%
“…Teachers need to view data use as related to their classroom activities and their instruction, instead of as a compliance activity independent of their classroom actions. On the other hand, studies found that social pressure by means of encouragement by the principal positively influenced data use (Schildkamp & Kuiper, 2010;Schildkamp & Teddlie, 2008;Schildkamp & Visscher, 2010;Schildkamp et al, 2012).…”
Section: Subjective Normsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ook deze doelen kunnen voortvloeien vanuit een verantwoordingsperspectief, zoals het gebruik van informatie om leerkrachten ter verantwoording te stellen voor de onderwijskwaliteit op school of om de schoolkwaliteit te verantwoorden ten opzichte van de onderwijsinspectie (Coburn & Talbert, 2006;Schildkamp & Kuyper, 2010;Wayman & Stringfield, 2006), of vanuit een schoolontwikkelingsperspectief, zoals het gebruik van informatie om de schoolkwaliteit te monitoren, verbeteracties voorop te stellen of voor beleidsontwikkeling en -planning (Coburn & Talbert, 2006;Schildkamp & Kuyper, 2010;Schildkamp, Rekers-Mombarg, & Harms, 2012).…”
Section: Doelen Met Betrekking Tot Informatiegebruikunclassified